Secondary plant compounds and forage evaluation - Reed, J.D.; Krueger, C.; Rodríguez, G.; Hanson, Jean (CAB International, 2000)
This chapter reviews the extensive literature on the toxicity and nutritional effects of secondary plant compounds (SPC) in forages. It discusses results from the research on two forages, Sesbania sesban and Trifolium pratense (red clover), as a way of illustrating the effects of SPC on forage evaluation. The main topics of discussion are plant polyhenols and protein digestion in ruminats; secondary plant compounds in the evaluation of red clover; and secondary plant compounds and the evaluation of sesbania.